Pilot implementation of a telehealth safety planning group intervention for suicidal rural Veterans enhanced by lived experience veteran peer participation - Goodman, Marianne; Strouse, Madison; Boucher, Caroline; Glatt, Sofie; Jacobs, James; Waliski, Angie; Fonseca, Emilia; Osterberg, Terra; Patel, Sapana (Frontiers in Psychiatry, 2025)
Despite the Veterans Administration (VA) designating suicide prevention as the number one clinical priority, Veteran suicide rates continue to rise. One sub-population at elevated risk are Veterans living in rural communities given their heightened availability of firearms coupled with more limited access to mental health services. Telehealth delivery of treatment is a potential solution for the provision of critical services to rural areas. Despite the expansive growth of virtual treatment after the pandemic, there exist few suicide-specific telehealth health services. Our community case study aims to address this gap by piloting a manualized suicide safety planning and firearm safety group, titled Project Life Force (PLF), delivered virtually to rural Arkansas. The project’s goal was to specifically enhance rural Veteran engagement with telehealth delivery through the use of community-based lived-experience rural peers. We present the rationale and details of the PLF intervention with a focus on the community Veteran peer enhancement component. This case study presents an innovative treatment design of a group led by a clinician augmented by a peer recovery leader that facilitated detailed conversations of how to limit suicide risk, encouraged disclosure about suicide symptoms, and promoted suicide related coping including encouragement of help-seeking behavior and safer storage of firearms. While the inclusion of a peer recovery leader was felt to be instrumental to the PLF-PE group’s success, special attention to the peer recovery leader is essential and includes specific training, regular supervision as well as attention and support regarding the psychological impacts of self-disclosure and assuming a leadership role. This case study highlights the invaluable role that lived experience peers can play in suicide prevention treatment efforts and lethal means safety and paves the way for continued development of this effort.